Minutes of General Council (extract)
010-0159-001 EXTRACT FROM THE MINUTES OF THE GENERAL COUNCIL, 22ND JULY 1936. Message to Spain. Mr. Bromley suggested sending a message of encouragement to the Government in Spain. It was explained that the Special Conference on Unemployment Regulations, held on the 20th July, had already sent a message to Spain. The National Council of Labour had decided that as soon as the Spanish Government were successful, a message of congratulation would be sent to the Trade Union and Socialist comrades. Further discussion took place, and IT WAS AGREED that a telegram of congratulation should be sent to the Spanish Trade Unionists and Socialists when it was considered to be the right moment by the two National Secretaries. 292/946/10/172